SOCIO-PSYCHOLOGICAL CRITERIA FOR THE FORMATION OF A PSYCHOLOGICAL PORTRAIT IN THE PREPARATION OF PERSONNEL FOR INNOVATIVE MANAGEMENT - Abdullajonova, Dilnoza (Журнал Педагогики и психологии в современном образовании, 2025)
This article discusses the problems, importance and relevance of personnel formation in environmental and economic management. The criteria for the formation of personnel in this direction in Uzbekistan will be revealed, that is, the emotional and psychological characteristics of such female cadres. The training program reveals the influence of communicative, organizational characteristics on women's activity and trends in the growth of management style, broken down by types of leadership in the ecological and economic direction. The study showed that women can use effective communication methods to listen to the team, enter into inter-organizational relationships and fulfill agreements on land resources, environmental and economic issues. A clear classification of the goals and personal style of women's leadership types in the activities of the land economy, the degree of mutual development of communicative and organizational skills in environmental and economic activities is shown.